Information Technology in India - Punj, Divya (International Journal of Psychosocial Rehabilitation, 2019)
India's information technology service industries may trace their roots back to a 10-year plan developed by the Electronics Committee, popularly known as the "Bhabha Committee," and covering the years 1966–1975. In 1967, in Mumbai, Tata Consultancy Services was founded; by 1977, thanks to a partnership with Burroughs, the company had begun exporting IT services from India. SEEPZ, the ancestor of today's IT parks, was founded in Mumbai in 1973. In the 1980s, more than 80% of all software exported from the nation came out of SEEPZ.The Task Force completed its detailed background study on the condition of technology in the nation and its IT Action Plan with 109 recommendations within 90 days of its inception. The Task Force was able to move fast because it drew on the insights of local and federal governments as well as academic institutions and the software sector. The World Trade Organization, the International Telecommunication Union, and the World Bank all shared similar views and made similar suggestions; therefore, many of their proposals were accepted. The Task Force also took into account lessons learned from Singapore and other countries that have carried out comparable initiatives. It required less creative thinking and more motivation to act on an established agreement in the networking industry and government